The Effect of the LOK-R Learning Model on Improving Multimodal Literacy Skills in Social Science Learning for Seventh Grade Students at MTsN 1 Surabaya - Katon Galih Setyawan, S.Sos., M.Sosio.; Dr. Nuansa Bayu Segara, S.Pd., M.Pd.; Dr. Hendri Prastiyono, M.Pd.; Aisyah Ayu Nararya (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to determine the process of improving multimodal literacy skills in social studies learning on the topic of Meeting Needs using the LOK-R learning model and to determine the effect of the LOK-R learning model on improving multimodal literacy skills in social studies learning among seventh grade students at MTsN 1 Surabaya. This study used a quantitative method designed using a Quasi-Experimental Design group experiment (Class VII G) and control group (Class VII I)). This study was supported by Vygotsky's social constructivism theory related to social interaction, ZPD, and scaffolding in the learning process. The instrument to stimulate various modes of communication, including text, visual, audio, and audio-visual, to determine the improvement in students' multimodal literacy skills. In addition, there was another instrument, namely an observation instrument tailored to multimodal indicators, which was used to determine the learning process in the classroom in improving students' multimodal literacy skills. The prerequisite test was conducted using question validity and reliability tests. Data analysis was performed using normality tests, homogeneity tests, and non-parametric tests (non-normal data) using the Mann-Whitney test to test the significance of the learning model and the N-gain test to determine the effectiveness of the learning model. The results of this study indicate that the LOK-R learning model has an effect on improving the multimodal literacy skills of seventh-grade social studies students at MTsN 1 Surabaya.